Natural attenuation of soil with biodiesel and its potential ecotoxicological impacts - Dilarri, Guilherme [UNESP]; Mendes, Carolina Rosai [UNESP]; de Moraes Ruy Sapata, Vinícius [UNESP]; Tamada, Ivo Shodji [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Montagnolli, Renato Nallin; Bidoia, Ederio Dino [UNESP] (My University, 2022)
Petroleum and its derivatives cause numerous toxicity-related impacts on the environment. The evaluation of such impacts can promote adequate treatments of oil-based residues. A better understanding of the degradation of hydrocarbons aids researchers to predict the environmental impacts and the biodegradation processes that yield decreased toxicity levels. However, petroleum derivatives are not the sole matter of concern. Another important discussion targeting the environmental behavior of biodiesel should be brought up. Soil microorganisms may improve the biodegradation of hydrocarbons due to their diversity and robust enzymatic apparatus during natural attenuation processes. Still, some compounds can have their negative impacts on biota evaluated according to three parameters: ecotoxicological potential in soil (i), specific biodegradation processes (ii), and post-treatment bioassays (iii). This review presents how microbial biodegradation may ultimately affect the overall degradation of hydrocarbons.
Keywords: Bioassays; Bioremediation; Ecotoxicity; Fuels; Petroleum